Pengaruh Brand Awareness, Kualitas Produk, dan E-Word Of Mouth terhadap Minat Beli Konsumen pada Pusat Oleh-Oleh X - Nanik Widyaningsih; Brahma Wahyu Kurniawan; Kukuh Harianto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of Brand Awareness, Product Quality, and E-Word of Mouth on consumer purchase intention at Pusat Oleh-Oleh X. The selection of Pusat Oleh-Oleh X was based on considerations related to the characteristics and relevance of the souvenir center. This is a quantitative study with a population that is not definitively known in terms of the number of visitors to Pusat Oleh-Oleh X, located on Jl. Pamenang, Desa Toyoresmi, Kec. Ngasem, Kabupaten Kediri. The sample consists of 96 respondents, calculated using the Lemeshow formula. The analysis methods used in this study include descriptive statistics, validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis, with data processed using SPSS 25 (Statistical Product and Service Solution). This analysis aimed to test the effect of each independent variable on consumer purchase intention. The results of the study indicate that, partially, both Brand Awareness and E-Word of Mouth significantly influence consumer purchase intention at Pusat Oleh-Oleh X. This suggests that higher brand awareness and positive information spread through E-Word of Mouth increase consumer purchase intention. On the other hand, product quality does not have a significant effect on purchase intention at Pusat Oleh-Oleh X, although product quality remains a relevant factor in consumer purchasing decisions. Simultaneously, Brand Awareness, Product Quality, and E-Word of Mouth significantly affect consumer purchase intention at Pusat Oleh-Oleh X. These findings suggest that these factors interact with each other in influencing consumer purchasing decisions. Therefore, it is important for the management of Pusat Oleh-Oleh X to focus on increasing brand awareness and leveraging E-Word of Mouth to attract more consumers.